Paid Online Surveys in the Digital Economy: Jurisprudential Classification and Islamic Legal Ruling - Saba Mohammad Mustafa Al-Bool (Justicia Islamica, 2026)
This study examines the jurisprudential classification and Islamic legal ruling on participation in paid online surveys within the digital economy. It addresses the central question: what is the appropriate Islamic contractual framework for paid online survey transactions, and under what conditions does participation become shariah-compliant? Employing a qualitative method that integrates descriptive analysis of digital survey platforms, inductive reasoning from classical jurisprudential sources on juʿālah (reward-based contracts), and analytical application of these principles to contemporary digital labor practices, the study systematically investigates the contractual mechanisms underlying paid online surveys. The findings establish that such surveys are best classified as juʿālah contracts, wherein the platform acts as the employer (jāʿil), the registered participant as the worker (ʿāmil), the monetary or point-based compensation as the juʿl, and the completion of survey questions as the stipulated work. The study further determines that participation is permissible (ibāḥah) under sharia, subject to six jurisprudential conditions: free registration, a known and lawful reward, the absence of prohibited payments, the avoidance of prohibited content, the legal competence of participants, and adherence to sharia guidelines on freedom of expression. These findings advance the emerging field of Islamic digital economy jurisprudence by offering a coherent framework for evaluating digital labor platforms and providing practical guidance for Muslims engaging in contemporary online economic activities.